Direct stimulation of bone mass by increased GH signalling in the osteoblasts of Socs2(−/−) mice - Dobie, R (Bioscientifica Ltd, 2014)
The suppressor of cytokine signalling (Socs2 (−/−))-knockout mouse is characterised by an overgrowth phenotype due to enhanced GH signalling. The objective of this study was to define the Socs2 (−/−) bone phenotype and determine whether GH promotes bone mass via IGF1-dependent mechanisms. Despite no elevation in systemic IGF1 levels, increased body weight in 4-week-old Socs2 (−/−) mice following GH treatment was associated with increased cortical bone area (Ct.Ar) (P<0.01). Furthermore, detailed bone analysis of male and female juvenile and adult Socs2 (−/−) mice revealed an altered cortical and trabecular phenotype consistent with the known anabolic effects of GH. Indeed, male Socs2 (−/−) mice had increased Ct.Ar (P<0.05) and thickness associated with increased strength. Despite this, there was no elevation in hepatic Igf1 expression, suggesting that the anabolic bone phenotype was the result of increased local GH action. Mechanistic studies showed that in osteoblasts and bone of Socs2 (−/−) mice, STAT5 phosphorylation was significantly increased in response to GH. Conversely, overexpression of SOCS2 decreased GH-induced STAT5 signalling. Although an increase in Igf1 expression was observed in Socs2 (−/−) osteoblasts following GH, it was not evident in vivo. Igf1 expression levels were not elevated in response to GH in 4-week-old mice and no alterations in expression was observed in bone samples of 6-week-old Socs2 (−/−) mice. These studies emphasise the critical role of SOCS2 in controlling the local GH anabolic bone effects. We provide compelling evidence implicating SOCS2 in the regulation of GH osteoblast signalling and ultimately bone accrual, which maybe via mechanisms that are independent of IGF1 production in vivo.